Differences in nephrotoxicity risk and renal effects among anti‐viral therapies against hepatitis B. Issue 3 (4th December 2014) - Koklu, S.; Gulsen, M. T.; Tuna, Y.; Koklu, H.; Yuksel, O.; Demir, M.; Guner, R.; Dogan, Z.; Kucukazman, M.; Poyrazoglu, O. K.; Biyik, M.; Ozturk, N. A.; et al.
Summary Background Results are conflicting with respect to the renal effects of anti‐viral agents used for hepatitis B virus infection. Aim To compare short and long‐term renal effects in real‐life settings and to determine risk factors for renal impairment during treatment. Methods 2221 treatment‐naïve patients were enrolled. Among these, 895 (302 lamivudine, 27 telbivudine, 282 entecavir, 273 tenofovir and 11 adefovir initiated patients) had 'repeated measures' of creatinine (baseline, 1st, 6th, 12th and 24th month of treatment). Telbivudine and adefovir groups were excluded from further analysis because of the low number of patients. We calculated the glomerular filtration rate (GFR) using the Modification of Diet in Renal Disease (MDRD) formula at each time point. Hypophosphataemia was also recorded. Risk factors for renal impairment were analysed. Results Tenofovir caused a decline in GFR at each time point when compared to baseline levels. However, lamivudine and entecavir did not change GFR. GFR‐shifting from ≥90 to 60–89 mL/min/1.73 m2 was comparable among groups. The proportion of patients whose baseline creatinine increased more than 25% was comparable among all anti‐virals. GFR showed a decline in patients who switched from entecavir to tenofovir. One patient with compensated cirrhosis needed to change from tenofovir because of renal safety. Seven and three patients developed transient hypophosphataemia in the tenofovir and lamivudine groups, respectively. Conclusions Although tenofovir caused a decline in GFR, differences between the anti‐viral agents do not appear to be so impressive. In patients with and without renal risk factors at baseline, there is no impact of anti‐virals, including tenofovir.